Seismic Resistance and Displacement Mechanism of the Concrete Footing - Abdoullah Namdar; Yun Dong (Shock and Vibration)
A realistic seismic simulation of the concrete footing has been made by using finite element method (FEM) software called ABAQUS. The effect of concrete footing embedment in soil on concrete footing-soil foundation interaction has numerically been simulated for considering displacement, stress, strain, and seismic acceleration load response at the base of a concrete footing. The results showed that the height of embedded concrete footing in soil foundation controls (i) mechanism and magnitude of lateral, vertical, and differential displacements of the concrete footing, (ii) strain energy, the acceleration load response, and stress paths, and (iii) concrete footing-soil foundation interaction. Compared with various theoretical and experimental results reported in the literature, the present study provides realistic seismic behavior of concrete footing-soil foundation interaction.